2013
DOI: 10.5172/conu.2013.45.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Attributes of clinical leadership in contemporary nursing: An integrative review

Abstract: Effective clinical leadership is offered as the key to healthy, functional and supportive work environments for nurses and other health professionals. However, as a concept it lacks a standard definition and is poorly understood. This paper reports on an integrative review undertaken to uncover current understandings of defining attributes of contemporary clinical leadership in nursing. Data collection involved a search of relevant electronic databases for a 10-year period. Keywords for the search were 'clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
72
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 34 publications
8
72
0
Order By: Relevance
“…In the review of Mannix et al it is demonstrated that definitions of CL have a clinical focus, a follower/team focus or a personal qualities focus. [15] Most CL characteristics include attributes reflecting technical and practical skills necessary for competent clinical practice and leading a team. Howieson and Thiagarajah [63] found that most literature is centered on recommended leadership behaviour, traits and competencies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the review of Mannix et al it is demonstrated that definitions of CL have a clinical focus, a follower/team focus or a personal qualities focus. [15] Most CL characteristics include attributes reflecting technical and practical skills necessary for competent clinical practice and leading a team. Howieson and Thiagarajah [63] found that most literature is centered on recommended leadership behaviour, traits and competencies.…”
Section: Discussionmentioning
confidence: 99%
“…Lacking a standard definition, CL is generally poorly understood. [15] Nevertheless it is a much used term. The National Health Service in Scotland [16] refers to CL within a clinical domain and describes CL in terms of driving service improvement and effective management of teams to provide excellence in patient care.…”
Section: -Reformulating the Conceptmentioning
confidence: 99%
“…2 Effective CL is a prerequisite for understanding the complex system of care for the benefit of patients and ensuring healthy workplaces 34 Conversely, ineffective CL has a negative impact on the healthcare workers and standard of care and can lead to adverse events 45 There is a need to compensate for the absence of the conventional mentor-to-apprentice transfer of CL knowledge and skills.…”
Section: Introductionmentioning
confidence: 99%
“…Previous CL programmes have demonstrated development of self-reported and observer-reported behaviours of CL competencies,14 improved safety and quality of care,11 development of individual skills and influence on workplace culture 1516 The training programmes have centred on leadership behaviours/traits and competencies; however, evidence of the impact of such programmes on the operational level is scarce 417…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation